Multiple Buddhisms in Ladakh: Strategic Secularities and Missionaries Fighting Decline - Elizabeth Williams-Oerberg (MDPI AG, 2021)
During fieldwork in Ladakh in July–August 2018, three authors from Asian studies, anthropology, and religious studies backgrounds researched “multiple Buddhisms” in Ladakh, India. Two case studies are presented: a Buddhist monastery festival by the Drikung Kagyü Tibetan Buddhist sect, and a Theravada monastic complex, called Mahabodhi International Meditation Center (MIMC). Through the transnational contexts of both of these case studies, we argue that Buddhist leaders adapt their teachings to appeal to specific audiences with the underlying goal of preserving the tradition. The Buddhist monastery festival engages with both the scientific and the magical or mystical elements of Buddhism for two very different European audiences. At MIMC, a secular spirituality mixes with Buddhism for international tourists on a meditation retreat. Finally, at MIMC, Thai Buddhist monks learn how to fight the decline of Buddhism through missionizing Theravada Buddhism in this land dominated by Mahayana and Vajrayana Buddhism. Paying attention to this multiplicity—to “multiple Buddhisms”—we argue, makes space for the complicated, ambiguous, and at times contradictory manner in which Buddhism is positioned in regards to secularism and secularity.